(untitled) (International Journal of Food and Nutritional Sciences, 2022)
According to conventional financial theories, people should carefully weigh risk and return considerations before making investment decisions to maximize their benefits and minimize losses. The classic economic theory is contested by behavioural finance, which contends that various biases influence each investor’s investing choices. They consist of regret, dislike, building, and dispositional effects as developed by the theory of prospecting, as well as heuristic biases, including anchoring, representativeness, gamblers fallacy, and more. The goal of the study article is to comprehend how these biases affect the process of making investment selections and what efforts can be taken by individual investors to make logical choices. The study suggests that individual traders must thoroughly mine data and consider external aspects before initiating investments after analyzing how practical concerns restrict individual decision-making. This article briefly presents the concepts of traditional banking and behavioural finance. The basic tenets of behavioural finance are the psychology